Effects of thermal stress on the photoinactivation and repair of photosystem II in a xanthophyll cycledeficient green alga - Leandro, Filipa Ferreira (2021)
Photosynthesis and primary productivity are very temperature-dependent. Extremely high or low temperatures affect the enzymatic mechanisms of photoprotection (xanthophyll cycle) and exacerbate the photo-imaging effects of high light on photosystem II (PSII). A recently proposed hypothesis states that abiotic stress, including mild cold and heat, enhances photoinhibition of photosynthesis not by directly damaging the PSII, but by inhibiting repair mechanisms. This work intends to test this hypothesis in an as yet unexplored group of green algae (Bryopsidales) without a xanthophyll functional cycle. In order to test this hypothesis, we used the measurement of chlorophyll fluorescence, under light and thermal stress, and subsequent quantification of D1 protein, using the Western blot technique. Our findings showed that for this group of algae, the aforementioned hypothesis is not applicable, as the abiotic stresses affected not only repair mechanisms but also exacerbated photoinhibition. Consequently, the group of green algae (Bryopsidales) showed great potential for future studies in the scope of the investigation regarding repair mechanisms of photosystem II.